The study on secretion of cytokine interleukin-4, interleukin-10 and interferon-γ in peripheral blood of multiple sclerosis patients - Li-yan QIAO; Xian-hao XU; Shi-fang HOU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective Multiple sclerosis (MS) is a mainly cell-mediated autoimmune demyelinating disease in central nervous system (CNS), characterized by inflammatory demyelinating and infiltration of mononuclear cells around microvessels in CNS. It has been shown that MS is caused by the imbalance between T helper cell 1 (Th1) and Th2 or between inflammatory cytokines and anti-inflammatory cytokines. However, the profile of cytokine according to the published data is contradictory. This study is to evaluate the status of cytokines from mononuclear T cells in MS patients and try to provide clues for clinical diagnosis and treatment.  Methods Enzyme-linked immunospot assay (ELISPOT) was used to test the spontaneous and antigen-specific [concanavalin A (ConA), myelin basic protein (MBP) and acetyleholine receptor (AChR)] Th1-related cytokine interferon-γ (IFN-γ) and Th2-related cytokines interleukin-4 (IL-4), IL-10 in the peripheral blood mononuclear cells in MS patients, who had not received any immunological treatment over the last 3 months.  Results Compared with normal controls and patients with non-immune neurological diseases, MBP specific IL-4, IL-10 and IFN-γ of MS patients increased significantly (P = 0.000, for all). In addition, MBP specific IFN-γ level of MS patients increased signicantly in acute or exacerbating phase when compared with that in stable phase (P = 0.002), while MBP specific IL-4 and IL-10 levels did not differ significantly (P > 0.05, for all).  Conclusions The examinations of IL-4, IL-10 and IFN-γ cytokines using ELISPOT are helpful for the differential diagnosis and the disease course of MS.   doi: 10.3969/j.issn.1672-6731.2014.10.008